2004
DOI: 10.1002/eat.20009
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of rehospitalization after total weight recovery in adolescents with anorexia nervosa

Abstract: The variables most clearly related to readmission were young age, abnormal eating attitudes, and a low rate of weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 20 publications
5
80
4
1
Order By: Relevance
“…37 Evidence currently confirms that a slow rate of weight gain in treatment as well as a low BMI at discharge predicts poor long term outcomes and readmissions. 40,46,76,77 Given that, as this study suggests, persons with AN differ in their short-term outcomes based on RFC, a variable known at the time of admission and modifiable through RFC-specific treatment interventions, further research should assess whether stage of change focused treatment can affect RFC, the associated outcomes, and LOS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Evidence currently confirms that a slow rate of weight gain in treatment as well as a low BMI at discharge predicts poor long term outcomes and readmissions. 40,46,76,77 Given that, as this study suggests, persons with AN differ in their short-term outcomes based on RFC, a variable known at the time of admission and modifiable through RFC-specific treatment interventions, further research should assess whether stage of change focused treatment can affect RFC, the associated outcomes, and LOS.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, weight gain in treatment at a rate that is too slow has been correlated with readmission to hospital. 46 Length of stay has been correlated with insurance status suggesting that a person's ability to pay for treatment influences how long they will be treated at a higher level of care. 47 This raises issues concerning fairness and the constraints on healthcare providers' abilities to carry out evidence-based clinical decisions regarding the appropriate setting and duration of care.…”
Section: Length Of Staymentioning
confidence: 99%
“…He also found that longer duration of the follow up and younger age at onset of the illness were associated with better outcome. However, a different study 8 found that lower age at onset was predictive of readmission of patients within 12 months of completing their initial treatment. Contrary to these findings, another study 9 found that age at onset was not a significant predictor of outcome.…”
mentioning
confidence: 94%
“…Previous research into recovering from AN has predominantly focused on defining the recovery from AN the patient perspective [1][2][3][4][5][6] and looked at predictors of recovery using quantitative criteria such as length of treatment and follow up or age at onset [7][8][9] with mixed results.…”
mentioning
confidence: 99%
“…la mayor o menor ganancia ponderal es bastante impredecible 4 , existiendo, además, una falta de consenso al fijar el objetivo de recuperación en adolescentes en desarrollo, habiéndose propuesto el uso de percentiles de IMC y fijado un rango entre 14 y 39 como objetivo inicial 28 . La inadecuada recuperación ponderal, actitudes alimentarias anómalas y baja edad, se han relacionado con rehospitalizaciones 29 , siendo la adecuada ganancia ponderal el mejor predictor, a corto plazo, de menor deterioro clínico 30 . Un mejor peso inicial también se ha relacionado positivamente con un mejor mantenimiento posterior del mismo 31 y, a largo plazo, la normalización ponderal y del estado nutricional parecen también determinantes de un buen pronóstico 32 .…”
Section: Objetivos Terapéuticosunclassified